2021
DOI: 10.3389/fphys.2020.596896
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Circulating Irisin Response to Ice Swimming and Body Composition in People With Regular Exercise Experience

Abstract: Severe cold exercise involves the irisin response, and may be related to body composition. We aimed to investigate changes in circulating irisin after ice swimming (IS), as well as to evaluate the correlation between body composition and the change in irisin caused by IS (Δirisin). 81 ice swimmers were recruited to perform IS activities. Blood samples were drawn 30 min before and 30 min after IS, and the serum levels of irisin and the ice swimmers’ body composition were measured. As results, circulating irisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…On the other hand, PTH may be involved in adipose tissue metabolic and/or thermogenic activation under cold conditions, and Kovaničová et al (2020) have shown a negative association between the increase of PTH induced by IS and visceral adiposity. We analyzed the relationship between our body composition data (detection method reported previously, Mu et al, 2020) and PTH, and found that PTH is indeed negatively correlated with visceral fat area (r = −0.2364, p = 0.0275, Spearman's analysis), and PTH is also negatively correlated with waist to hip ratio (r = −0.2285, p = 0.0333, Spearman's analysis). This suggested IS induced PTH changes are beneficial to fat utilization.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, PTH may be involved in adipose tissue metabolic and/or thermogenic activation under cold conditions, and Kovaničová et al (2020) have shown a negative association between the increase of PTH induced by IS and visceral adiposity. We analyzed the relationship between our body composition data (detection method reported previously, Mu et al, 2020) and PTH, and found that PTH is indeed negatively correlated with visceral fat area (r = −0.2364, p = 0.0275, Spearman's analysis), and PTH is also negatively correlated with waist to hip ratio (r = −0.2285, p = 0.0333, Spearman's analysis). This suggested IS induced PTH changes are beneficial to fat utilization.…”
Section: Discussionmentioning
confidence: 87%
“…The research process was as previously described (Mu et al, 2020). Briefly, all participants were divided into three groups, and each group performed the exercise session at a different place and on a different day.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Several studies showed increased irisin levels after exercise, suggesting positive effects of exercise on cardiovascular, skeletal, and muscular systems (60,61). However, some other studies observed a decrease in irisin levels after various types of physical activity (62)(63)(64)(65)(66) whereas some others reported no changes in irisin levels in different exercise programmes (67,68). In addition to these controversial findings, in vitro study did not support the proposed role of exercise-related signalling pathways in irisin regulation in human skeletal muscle (69).…”
Section: Discussionmentioning
confidence: 99%
“…It could be also related to the sea and air temperature at the time of the dive since they were lower when the first and third dives were performed as compared to the fifth dive. Although Bubak and collaborators reported no influence of the temperature in which exercise takes place on plasma irisin level ( 74 ), another study suggested increased consumption of irisin due to cold exposure and consequently decreased serum levels ( 66 ). It would be interesting to explore whether further dives would lead to the additional reduction in serum irisin levels (the pre-dive values) despite reversed trend observed after the fifth dive or the observed increase represents a turn-point that reverses the trend and lead to the return of the irisin levels to the initial values observed at the beginning of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The study examined changes in serum irisin concentration after swimming in cold water. Interestingly, when cold was combined with exercise, winter swimmers unexpectedly experienced a significant decrease in serum levels of irisin [18], possibly due to different tissue sources and the metabolic environment of irisin. In addition, physical exercise does not always play a positive role in the metabolic processes of the body and may cause increased expression of some inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%